Academia Versus Practice? Toward a Debate on the Value of Academic Education in the German-Speaking Hospitality Industry. Issue 4 (2nd October 2018) - Gardini, Marco Adelmo
ABSTRACT: Consequences of the growing maturity of the hospitality industry are increasing levels of competition, complexity, and change in many hospitality markets. This leads to new managerial challenges for hospitality companies, and the future managerial skills needed by managers in the industry reflect these changes. Hence, the question is being raised whether there is an increasing necessity for more advanced management skills and whether the traditional educational profiles and programs in hospitality education in Germany, Austria, and Switzerland have to be realigned. In consequence, there might be a need for a paradigm shift concerning the perception of the overall value of an academic education in hospitality in German-speaking countries. As a result, this article aims to depict the necessity of a joint effort between academia and industry to support the value and the demand for an advanced academic education in the German-speaking hospitality industry.